ANALYSIS OF TRANSIENT RECOVERY VOLTAGE ON SURALAYA-SURALAYA BARU 500 KV TRANSMISSION LINE DUE TO ADDITIONAL SERIES REACTORS - Mayla Sari, Ika
The higher growth of electricity generation and power grids will impact the increase in short-circuit currents. In large systems such as Java-Madura-Bali, the short circuit problem is a concern because it can damage electrical equipment if it exceeds the short circuit current withstand of the equipment. One of the mitigations to reduce the magnitude of the short circuit current is to install series reactors. However, it is feared that the addition of significant series reactors will increase the value of the transient recovery voltage when the circuit breaker interrupts the short circuit current. This research was conducted to conduct a transient recovery voltage analysis to review the effects of installing series reactors on Suralaya-Suralaya Baru 500 kV transmission line 2030 as part of the Java-Madura-Bali system. In the simulation after adding the series reactor, it was found that the TRV and RRRV values were 922,2 kV and 11,9 kV/?s respectively. The TRV value is still within the safe limits of the IEEE C37.011 calculation standard for short line fault, while the RRRV value has exceeded the standard safe limits.